Die Weinstockrede Jesu und die missionstheologische Relevanz der gegenseitigen Liebe (Joh 15.1–17) - Hentschel, Anni 1972- (2022)
The Johannine commandment of love aims not only in an ethical-ecclesial sense at the cohesion in the church, but in a mission-theological sense at the winning of new church members. Jn 15.1-17 explains how the mutual immanence of God, Jesus and his disciples enables his followers to gain new fruit in the sense of new church members through mutual love. This continues the christological-ecclesial interpretation of Jesus’ foot-washing from John 13. The symbolic action illustrates how Jesus’ mission leads to the foundation of a community of disciples as a community of love, which becomes the place where the love of God can be permanently experienced (13.1-20, 34-5). The disciples are commissioned to make love present in the world. They are equal among themselves in their immediacy to Jesus, as members of the community of discipleship. A mission-theological use of the harvest metaphor is already found prominently in John 4.35-8 and 12.24-6 and thus in two texts, each of which describes the mission of the followers in correspondence to the mission of Jesus. The vine metaphor deepens that and how Jesus’ followers are to contribute to the enlargement of the community of followers even after his departure, whereby the pre-Easter community of followers is the model for the post-Easter community.
Das johanneische Liebesgebot zielt nicht nur in einem ethisch-ekklesiologischen Sinn auf den Zusammenhalt in der Gemeinde, sondern in einem missionstheologischen Sinn auf die Gewinnung neuer Gemeindeglieder. Joh 15.1-17 erläutert, wie die gegenseitige Immanenz von Gott, Jesus und den Seinen die Nachfolgegemeinschaft befähigt, durch die wechselseitige Liebe neue Früchte im Sinn neuer Gemeindeglieder zu gewinnen. Damit wird die christologisch-ekklesiologische Deutung der Fußwaschung Jesu aus Joh 13 weitergeführt. Die zeichenhafte Handlung illustriert, wie Jesu Sendung zur Gründung einer Nachfolgegemeinschaft als Liebesgemeinschaft führt, die zu dem Ort wird, an dem die Liebe Gottes bleibend erkannt werden kann (13.1-20,34f.). Gefordert und beauftragt sind die einzelnen Jüngerinnen und Jünger, die in ihrer Jesusunmittelbarkeit untereinander gleichgestellt sind, als Mitglieder der Nachfolgegemeinschaft. Eine missionstheologische Verwendung der Erntemetaphorik findet sich bereits prominent in Joh 4.35-8 und 12.24-6 und damit in zwei Texten, die jeweils die Sendung der Nachfolgenden in Entsprechung zur Sendung Jesu beschreiben. Die Weinstockrede vertieft, dass und wie die Seinen auch nach Jesu Abschied zur Vergrößerung der Nachfolgegemeinschaft beitragen sollen, wobei die vorösterliche Nachfolgegemeinschaft Vorbild der nachösterlichen Gemeinde ist.
Keywords: Jesus’ foot-washing; Johannine Christology; Johannine ecclesiology; Discipleship; the new commandment; the vine metaphor